Respuesta :
Answer: [tex]d=-1/4[/tex]
Step-by-step explanation:
Simplify both sides of the equation
[tex]6d+-11/2=2d+-13/2[/tex]
Subtract 2d from both sides
[tex]6d+-11/2-2d=2d+-13/2-2d[/tex]
[tex]4d+-11/2=-13/2[/tex]
Add 11/2 to both sides
[tex]4d+-11/2+11/2=-13/2+11/2[/tex]
Divide both sides by 4
[tex]4d/4=-1/4[/tex]
Get your answer
[tex]d=-1/4[/tex]
Answer:
-1/4
Step-by-step explanation:
6d-11/2=2d-13/2
Collect like terms
6d-2d=11/2-13/2
4d=11/2-13/2
4d=(11-13)/2 Using LCM
4d=-2/2
4d=-1
Divide both sides by 4
4d/4=-1/4
d=-1/4
To check if the answer is correct, substitute d with -1/4. And then both sides of the equation must be equal
6d-11/2=2d-13/2
6(-1/4)-11/2=2(-1/4)-13/2
-6/4-11/2=-2/4-13/2
Let's put the figure with the same denominator in the same side of the equation
-11/2+13/2=-2/4+6/4
(-11+13)/2=(-2+6)/4
-2/2=-4/4
-1=-1